Kreatifitas Guru Matematika dalam Mengembangkan Program Pembelajaran Secara Daring - Yulia Haryono; Rahmi Rahmi; Radhya Yusri (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The development of learning during the current Covid-19 pandemic demands there is a change in learning for teachers and students to adapt existing situation. Of course, with this, it is undeniable, that very play a very important role, namely technology, and information for learning activities at school. One of them is learning media that can be used as a teacher’s teaching aid to make it easier for student to understand the material being taught and clarify the presentation of massages and information from the teacher to the teacher students so that the teaching and learning process runs smoothly. Through training this teacher is more motivated, creative, and innovative in developing online learning so that students better understand the material at home independently and interested in what is presented by the teacher online.